Pathological Study of Blood Parasites in Rice Field Frogs, Hoplobatrachus rugulosus (Wiegmann, 1834) - Achariya Sailasuta; Jetjun Satetasit; Malinee Chutmongkonkul (Veterinary Medicine International)
One hundred and forty adult rice field frogs, Hoplobatrachus rugulosus (Wiegmann, 1834), were collected in Srakaew province, Thailand. For blood parasite examination, thin blood smears were made and routinely stained with Giemsa. The results showed that 70% of the frogs (98/140) were infected with 5 species of blood parasites, including a Trypanosoma rotatorium-like organism, Trypanosoma chattoni, Hepatozoon sp. a, Hepatozoon sp. b, and Lankesterella minima. Pathological examination of the liver, lung, spleen, and kidney of the frogs that were apparently infected with one of these blood parasites were collected and processed by routine histology and subsequently stained with haematoxylin and eosin. Histopathological findings associated with the Trypanosoma rotatorium-like organism and Trypanosoma chattoni-infected frogs showed no pathological lesions. Hepatozoon sp. a and Hepatozoon sp. b-infected frogs developed inflammatory lesions predominantly in the liver, demonstrating granuloma-like lesions with Hepatozoon sp. meronts at the centre. Tissue sections of Lankesterella minima-infected frogs also showed lesions. Liver and spleen showed inflammatory lesions with an accumulation of melanomacrophage centres (MMCs) surrounding the meronts and merozoites. It is suggested that Hepatozoon sp. a, Hepatozoon sp. b, and Lankesterella minima-infections are capable of producing inflammatory lesions in the visceral organs of rice field frogs, and the severity of lesions is tentatively related to levels of parasitemia.